Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.

- anonymous

(x – 3)2 = 2

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions.

Get your **free** account and access **expert** answers to this and **thousands** of other questions

- anonymous

(x – 3)2 = 2

- jamiebookeater

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions

- anonymous

distribute the 2 so it would be|dw:1366645202678:dw|

- anonymous

or are you saying its ^2 not 2

- anonymous

|dw:1366645220762:dw| ^2 <-

Looking for something else?

Not the answer you are looking for? Search for more explanations.

- anonymous

ahh, well that just means that you are doing (x-3)(x-3)=2

- anonymous

I got this x = 3 ± sqrt 2

- anonymous

:) or :(

- anonymous

how did you get that? im not knocking whether it is right or wrong i just wanna know how you did it

- anonymous

x2^-6x+9=2
x=3+-sqrt2

- anonymous

new problem now?

- anonymous

Sam’s plasma TV has a 14 in by 18 in screen with a plastic trim border. The total area of the TV and border is 480 in2. How wide is the trim around the TV?

- anonymous

good.

- anonymous

how would you go about your new problem?

- anonymous

w = width of border
(14 + w)(18 + w) = 480
252 + 32w + w^2 = 480
w^2 + 32w - 228 = 0
( w + 38)(w - 6) = 0
so w = -38 (impossible) or w = 6
6 in

- anonymous

there you go :)

- anonymous

Part 1: Solve the following equation using one of the methods listed below. Show all work. (4 points)
Part 2: Using complete sentences, explain why you chose the method you used. (2 points)
Equation:
0 = x2 + 6x + 3

- anonymous

okay, how would you solve it?

- anonymous

x²+6x+3=0
x² +6x +9 +3 =9 (Add the square of 1/2 the coefficient of x to both sides.)
x²+6x +9 = 6 (Simplify)
(x+3)²=6 (Write the trinomial as a perfect square.
x+3 = ±√6 (Take the square root of both sides.)
x=-3 ±√6 (Simplify)
I choose completing the square because it requires less arithmetic than the other common method of using the quadratic formula. Graphing would not produce an accurate answer and since it cannot be factored into whole numbers, that method is not desirable.

- anonymous

haha you get this stuff :) why are you asking for help

- anonymous

just some were difficult thats all

- anonymous

ahh well you seem to me you are gonna get an A :D

Looking for something else?

Not the answer you are looking for? Search for more explanations.